PENGUATAN LEGALITAS PRODUK UMKM DESA PADAASIH MELALUI EDUKASI SERTIFIKASI HALAL - irham, Muhammad Irham Taufik; Juhana, Riyadi; Rumdiana, Yayan; Nafia, Isya; Khoirunnisa, Aulia; Rufitasari, Rasya (JURNAL PENGABDIAN KEPADA MASYARAKAT (JPKM) KEBANGSAAN, 2025)
MSMEs have a strategic role in national economic development, but still face various challenges, especially in terms of legality and improving product quality. One aspect of legality that is important, but has not been widely accessed by MSMEs in Padaasih Village, West Bandung Regency, is halal certification. In fact, halal certification not only guarantees religious aspects, but also increases consumer confidence and product competitiveness in domestic and international markets. This community service activity aims to increase the understanding and capacity of MSME actors in the halal certification process and strengthening product quality through an educational and participatory approach. The activity was carried out at PKBM Bina Bangsa Berkarakter as a strategic local partner, involving 25 MSME players engaged in the food and beverage sector. Implementation methods include socialisation, simulation training for applying for halal certification, product quality training, and interactive discussions. The results of the activity showed a significant increase in participants' understanding of the procedures and benefits of halal certification. In addition, participants also gained basic skills in improving packaging and product quality according to food safety standards. The final evaluation showed that 92% of participants stated that the activity was very useful and encouraged their interest in taking care of product legality independently. This activity strengthens the role of PKBM as a community learning centre that can bridge MSMEs in accessing halal certification information and services.